Implementasi IPv6 untuk Remote Laboratorium Jaringan Komputer - Haryono, Nugroho Agus; Indriyanta, Gani; Luhulima, Mardonius Riel (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2024)
Computer network laboratory has become a crucial aspect in learning and practicals, although network device limitations remain the main challenge. Learning computer networks using simulators or emulators can save costs, but has limitations unlike using real devices. Learning using remote laboratories has become an alternative solution to the problem. Implementation of remote laboratories with IPv6 protocol using descriptive method approach has been successfully carried out. This implementation provides significant benefits for students in working on practicals remotely.Guided interviews were conducted to evaluate the comfort of using remote labs. The interview results for the evaluation of remote lab usage showed that the majority of respondents (81.3%) felt helped by the presence of network devices that can be remotely accessed with an IPv6 address. Meanwhile, a small portion (10.4%) of respondents preferred to use GNS3 or Packet Tracer. Regarding the problem of connecting to remote routers, the majority of respondents (52.1%) felt that the internet connection at their residence was very smooth for accessing remote devices in the Computer Network Laboratory. Conversely, 39.6% of respondents experienced problems with less smooth connections. 8.3% of respondents felt that their connection was not smooth, sometimes disconnected during configuration, potentially causing configuration failure.